Market Orientation And Product Innovation To Increase Competitive Advantages And Its Impact On Marketing Performance - Dikdik Harjadi; Dewi Fatmasari; Ayu Siti Nurhasanah (Al-Amwal : Jurnal Ekonomi dan Perbankan Syari'ah, 2020)
This study aims to find out the effect of market orientation and product innovation on competitive advantage in relation to marketing performance on food SMEs (Small Medium Enterprises) in Darma Sub-District, Kuningan District, West Java. By applying a total sampling method, 42 food SMEs in Darma Sub-District were selected as samples in this study. Meanwhile, the research method used in this study was descriptive-verificative method. Basically, there were thee variables in this study, namely; 1) dependent variable (Z) – in this case, performance marketing; 2) intervening variable (Y) – in this case, competitive advantage; and 3) independent variable (X) – which includes market orientation (X1) and product innovation (X2). The collected data were then analyzed by applying path analysis and IBM SPSS 21.0. The result showed that; 1) market orientation has a positive and significant effect on competitive advantage with value (0,029 < 0,05); 2) product innovation has a positive and significant effect on competitive advantage with value (0,000 < 0,05); 3) market orientation has a positive and significant effect on marketing performance with value (0,045 < 0,05); 4) product innovation has a positive and significant effect on marketing performance with value (0,033 < 0,05); and 5) competitive advantage has a positive and significant effect on marketing performance with value (0.000 < 0,05).